2007
DOI: 10.1086/519263
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Mortality in Necrotizing Community-Acquired Pneumonia Caused by Staphylococcus aureus Containing Panton-Valentine Leukocidin

Abstract: Airway bleeding, erythroderma, and leukopenia are associated with fatal outcome from Panton-Valentine leukocidin-positive S. aureus necrotizing pneumonia. More work is needed to develop more efficacious therapy against this highly lethal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
202
2
48

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(262 citation statements)
references
References 32 publications
10
202
2
48
Order By: Relevance
“…aureus is increasingly recognized as a signifi cant cause of complicated pneumonia. A recent study from France demonstrated a mortality rate of >50% in patients infected with S. aureus that contained Panton-Valentine leukocidin (PVL), which caused necrotizing pneumonia (37). A study among children from Houston demonstrated a marked increase in complicated pneumonia in patients with PVL-containing S. aureus infection (29).…”
Section: Discussionmentioning
confidence: 99%
“…aureus is increasingly recognized as a signifi cant cause of complicated pneumonia. A recent study from France demonstrated a mortality rate of >50% in patients infected with S. aureus that contained Panton-Valentine leukocidin (PVL), which caused necrotizing pneumonia (37). A study among children from Houston demonstrated a marked increase in complicated pneumonia in patients with PVL-containing S. aureus infection (29).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while leucopenia, a high level of serum creating kinase and C-reactive protein (>200 g/L), and a negative pneumococcus and Legionella antigen test can make invasive disease doubtful, it is simple and useful for physicians to estimate the pathogen by examining sputum Gram stains and verifying grape-like clusters. The characteristic feature of rapid progression to fatal pneumonia is hemoptysis, alveolar hemorrhage, leucopenia, hypoxia, and influenza-like illness, mainly in young adults and healthy children [12].…”
Section: Clinical Symptomsmentioning
confidence: 99%
“…National hospitalization rates for empyema in US children increased from 3 to 6 per 100,000 following the release of PCV-7 [49]. Experts posit that increased rates of complicated pneumonia result from more accurate diagnostic techniques and changes to the spectrum of pathogens responsible for pediatric CAP, as nonvaccine pneumococcal serotypes replace the conjugate vaccine serotypes and virulent strains of Staphylococcus aureus become more prevalent [50,51].…”
Section: Serology and Acute Phase Reactantsmentioning
confidence: 99%
“…Neurocognitively impaired children may be at increased risk for aspiration of these pathogens from the upper respiratory or GI tracts. Staphylococcus aureus is well described as a cause of severe necrotizing pneumonia in the literature, and is associated with leukopenia, erythroderma, purulent cough, and pulmonary hemorrhage [51,63].…”
Section: Diagnosis Of Necrotizing Pneumoniamentioning
confidence: 99%